Distribution of microbial population as a cause and consequence of the anti-bacterial therapy failure of ventilator-associated pneumonia - M. G. Chechenin; A. M. Volkov; D. A. Kudlay; V. N. Ilyina; M. N. Orlova; L. M. Samoylova; I. A. Suchkova (Туберкулез и болезни лёгких)
Goal of the study: to study the specific distribution of microbial population in the lungs in the patients being on artificial pulmonary ventilation for a continuous period of time basing on the results of bacteriological culture of the specimens collected from various parts of the lungs and tracheobronchial system through intravital broncoscopy or post mortem.Materials and methods. Pilot study including intravital and post mortem identification of microbial population in various parts of the lungs and tracheobronchial system in 18 patients with signs of ventilator-associated pneumonia developed after cardiac-vascular and neurosurgical interventions. Intravital microbiological tests of the aspirate collected from all lobar bronchi of both lungs obtained through fiber-optic bronchoscopy were performed in 9 patients. Post mortem collection of pulmonary tissue for culture from all lobes of both lungs, lingulars of the left lung and relevant bronchi (totally 12 specimens from the lungs and bronchi) during 24 hours after death was performed in 9 patients.Results of the study. As per the data of microbiological tests the pulmonary infection was found in all patients from both groups. Intravital tests detected inter-lobar differences of microbial profile in 5 cases, and in 4 cases the differences were detected between the lungs. Post mortem microbiological tests detected differences between lobes and within lobes in 6 cases, of them in 5 cases there were also differences between the lungs. In all cases of nonuniform distribution detected post mortem, differences between lobes were accompanied by the differences within lobes (between tissue of the lungs and draining bronchus). Data analysis of intravital and post mortem microbiological diagnostics detected the similarity in the microbial population distribution in the tracheobronchial system in case of ventilator-associated pneumonia despite the different techniques of specimen collection. The diagnostic test capable to reflect regional distribution of the microbial population has been offered: aspirate culture from 5 lobar bronchi which could be used when managing patients with ventilator-associated pneumonia.